Contrasting cultures of emergency department care: a qualitative study of patients’ experiences of attending the emergency department for low back pain in the UK - Catherine Pope; Clare Ryan; Lisa C Roberts (BMJ Open)
Objectives This article aimed to explore patients’ experiences of attending the emergency department (ED) for low back pain (LBP) and provides a theoretically informed analysis of the ED cultures perceived by patients to inform their experiences of care.Design Multisite, cross-sectional qualitative interview study.Setting Four NHS Emergency Departments located in the UK.Participants 47 adults (aged 23–79 years) who, in the past 6 weeks, had attended the ED for LBP (all types and durations). Purposive sampling was used to gain variation in the recruiting sites, and participants’ LBP and demographic characteristics.Interventions Data were collected using individual, semistructured, telephone interviews (median 45 min duration) which were audio-recorded and transcribed verbatim. Analysis was informed using reflexive thematic analysis and ideal type analysis. Cycles of inductive and deductive analysis were undertaken, with Bourdieu’s concepts of field and habitus employed to help explain the findings.Results We present three contrasting cultures of ED care for LBP, comprising (1) emergency screening only, (2) ‘cynicism and neglect’ and (3) appropriate and kind care. Taking each culture (field) in turn, we explore important differences in the content and delivery of care. Drawing on Bourdieu’s concepts of field and habitus, we consider the social and institutional norms and misrepresentations likely to underpin the thoughts and behaviours of ED staff (their habitus), and why these tended to vary based on where and by whom the patient was managed in the ED.Conclusions Strategies to improve patients’ experience need to review the social and institutional norms that underpin staff habitus, the assumptions informing these norms and the voices that validate and reproduce them.ISRCTN registration number ISRCTN77522923.